Development of Incubator Analyzer Using Personal Computer Equiped With Measurement Certificate - Laily Nurrohmah; Dwi Herry Andayani; Andjar Pudji (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2020)
Baby incubators are used for premature babies when babies are born prematurely. In order to ensure the accuracy of medical devices, periodic tests and controls are needed, which aim to reduce the risk of measurement. The baby incubator can be tested with a calibration device that is used to calibrate temperature, noise, humidity, and airflow so that the conditions remain stable and within normal limits. The purpose of this study is to develop a calibrator device based on a computer to measure noise and airflow parameters. The standard incubator analyzer is not equipped with a computer interfacing. Furthermore, it needs data processing via Excel. Therefore, in this study, an incubator analyzer device is proposed, which has four parameters to measure, namely, temperature, noise, humidity, and airflow. The main part of this design is the Atmega328 Microcontroller, in which the function is used as a data processor, equipped with Bluetooth communication and data storage. Furthermore, the output will be displayed in a computer unit. In this study, the noise was measured using analog sound Sensor V2; and have the most significant error at 37oC setting temperature that is equal to 0.17%. At the same time, the airflow parameter measured using an airflow sensor, type D6F-V3A01. Based on the measurement, the error was 0.5% at a temperature setting of 36oC and 37oC. The use of displays on personal computers and data processing using Excel allows users to monitor calibration and data processing. The feasibility of this device is proven. Therefore, this design can be used for baby incubator calibration.